Syndromic and Monogenic Obesity: New Opportunities Due to Genetic-Based Pharmacological Treatment - Kallirhoe Kalinderi; Vasiliki Goula; Evdoxia Sapountzi; Vasiliki Rengina Tsinopoulou; Liana Fidani (MDPI AG, 2024)
Obesity is a significant health problem with a continuously increasing prevalence among children and adolescents that has become a modern pandemic during the last decades. Nowadays, the genetic contribution to obesity is well-established. For this narrative review article, we searched PubMed and Scopus databases for peer-reviewed research, review articles, and meta-analyses regarding the genetics of obesity and current pharmacological treatment, published in the English language with no time restrictions. We also screened the references of the selected articles for possible additional articles in order to include most of the key recent evidence. Our research was conducted between December 2022 and December 2023. We used the terms "obesity", "genetics", "monogenic", "syndromic", "drugs", "autosomal dominant", "autosomal recessive", "leptin-melanocortin pathway", and "children" in different combinations. Recognizing the genetic background in obesity can enhance the effectiveness of treatment. During the last years, intense research in the field of obesity treatment has increased the number of available drugs. This review analyzes the main categories of syndromic and monogenic obesity discussing current data on genetic-based pharmacological treatment of genetic obesity and highlighting the necessity that cases of genetic obesity should follow specific, pharmacological treatment based on their genetic background.